Զրադաշտականության օրենքի ազդեցությունը Իրանի մշակույթի վրա իսլամից հետո - Հոսեյն Քաֆաշիան (ՀՀ ԳԱԱ հրատ.)
The study is devoted to the influence of the 4000-years old history of Zoroastrian beliefs on the Iranian culture both before and after Islam law. Zoroastrian beliefs still continue to influence even today.
Keywords: Geography; Anthropology; Recreation; Culture and Cultural Processes